Theoretical and Numerical Simulation Study on the Ultimate Load Capacity of Triangular and Quadrilateral Truss Structures - Xianquan Wang; Yong Qiu; Jie Yuan; Dongyan Liu; Peiyu Shi; Chenchen Zhao; Shanyuan Xu; Tengfei Zhao (Buildings, 2024)
Spatial truss structures (STSs), serving as the bottom support structure of a cooling tower, effectively harness the superior load-bearing capacity offered by lattice-type truss structures. STSs are composed of main bars, diagonal bars, and horizontal bars, with horizontal bars serving as vital components of the truss structure. They play a pivotal role in maintaining the overall integrity and stability of the structure. The proportional relationship between the stiffness of each bar in STSs has a profound impact on the mechanical characteristics of the overall structure. This relationship directly influences the ultimate load-bearing capacity of the structure. Therefore, conducting research on the influence patterns of this relationship is of utmost importance. This paper explores the study of triangular truss structures (TTSs) and quadrilateral truss structures (QTSs). Firstly, through theoretical analysis, considering structural elements such as the stiffness of the horizontal bars, the number of layers in the truss, and the angle between the diagonal bars and the horizontal bars, theoretical expressions for the calculation of the ultimate load capacity of TTSs and QTSs are derived. Furthermore, a parametric finite element (FE) model was established for the TTSs and QTSs. Through numerical simulations, the validity of the theoretical calculation expressions was verified. Finally, this paper discusses the influence of factors such as the stiffness of the horizontal bars, the number of layers in the truss, and the angle between the diagonal and horizontal bars on the TTSs and QTSs. It analyzes the patterns and trends of these influences. The research results indicate that the theoretical and numerical simulation results for the TTSs have an error ranging from 0.40% to 4.93%, while the relative error for the QTSs ranges from 1.59% to 4.88%. These errors are within an acceptable range for engineering calculations. As the stiffness of the horizontal bars increases, the proportionality coefficient of the truss’s ultimate load capacity shows an initial increase followed by a stable trend. It reaches an equilibrium state when the stiffness of the horizontal bars reaches a certain threshold. As the number of layers in the truss and the angle between the diagonal and horizontal bars increase, the proportionality coefficient of the load capacity gradually decreases. The research findings provide a theoretical basis for the application of TTSs and QTSs in cooling towers.